Reliable molecular differentiation of Trichuris ovis and Trichuris discolor from sheep (Ovis orientalis aries) and roe deer (Capreolus capreolus) and morphological characterisation of their females: morphology does not work sufficiently - Vejl, Pavel; Nechybová, Stanislava; Peřinková, Pavla; Melounová, Martina; Sedláková, Vladimíra; Vašek, Jakub; Čílová, Daniela; Rylková, Kateřina; Jankovská, Ivana; Vadlejch, Jaroslav; Langrová, Iva (Parasitology research, 2017)
The main aim of the study was to evaluate associations between morphological variability of Trichuris females from sheep and roe deer and their rDNA polymorphism in whipworm populations from the Czech Republic. The results introduced the use of new molecular markers based on the internal transcribed spacer (ITS)1-5.8S RNA-ITS2 region polymorphisms, as useful tools for the unambiguous differentiation of congeners Trichuris ovis and Trichuris discolor. These markers revealed both parasites in roe deer and in sheep; however, T. ovis females predominated in sheep while T. discolor females occurred mostly in roe deer. Additional analysis of ITS1-5.8 rRNA-ITS2 discovered the genetic uniformity of the analysed T. discolor but high haplotype variation of T. ovis. Simultaneously, molecularly designated female individuals of both species were categorised into four morphotypes (MT) on the basis of morphology of genital pore area. MT1 and MT4 (vulvar opening on everted vaginal appendage/on visible cuticular bulge) occurred only in T. ovis, MT2 (uneverted vagina-vulvar opening without any elevation) was identified only in T. discolor and MT3 (transient type of vulvar opening on a small swelling) was observed in both species. Statistical analysis of biometric data confirmed that morphology of vulva is not a reliable marker for the species determination. On the basis of the ITS1-5.8S RNA-ITS2 region variability, we carried out a phylogenetic analysis (maximum likelihood method, Hasegawa-Kishino-Yano model) which showed that T. ovis haplotypes from the Czech Republic and Ireland and T. discolor haplotypes from the Czech Republic, Spain, Iran and Japan are sister OTUs.
Keywords: Molecular Typing; Deer; Sheep; vysoká zvěř; DNA helmintů; DNA, Ribosomal; Phylogeny; polymorfismus genetický; ITS1-5.8S rRNA-ITS2 region; Female; Trichuris; DNA, Helminth; zvířata; Trichuriasis; Morphotypes; Polymorphism, Genetic; RNA ribozomální; Sheep Diseases; Trichuris ovis; ženské pohlaví; Trichuris discolor; Male; fylogeneze; RNA, Ribosomal; Czech Republic; molekulární typizace; Molecular markers; ribozomální DNA; Animals; trichurióza; Česká republika; mužské pohlaví; nemoci ovcí; ovce